Nhận dạng bậc hệ động lực - Lân, Vũ Như; Phu, Đặng Thành; Hưng, Vũ Chấn (Journal of Computer Science and Cybernetics, 2016)
Estimation of states and parameters has been developed by using the conjugate operator and two-stages filter for identification of order for dynamical systems.